Human thermal models for evaluating infrared images. - Kakuta, N. (IEEE Engineering in medicine and biology magazine)
Discusses comparing infrared images under various thermal environmental conditions through normalization of skin surface temperature. To evaluate IR images obtained under various thermal environmental conditions, we proposed a human thermal model with which IR images obtained under certain thermal environmental conditions can be converted into images under other conditions. The model was based on a numerical calculation of the bio-heat transfer equations that express heat transfer phenomena within the human body. A 16-cylinder-segment model was used as the geometry of the human body. Comparisons of IR images with their converted images indicate that this method is effective in eliminating the influence of the thermal environmental conditions. However, the difference between the converted images and the original ones varies among segments. In future work, we will use this method to investigate the IR images of several subjects under various thermal environments.